If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + 5(n + -11) = 7 Reorder the terms: N + 5(-11 + n) = 7 N + (-11 * 5 + n * 5) = 7 N + (-55 + 5n) = 7 Reorder the terms: -55 + N + 5n = 7 Solving -55 + N + 5n = 7 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '55' to each side of the equation. -55 + N + 55 + 5n = 7 + 55 Reorder the terms: -55 + 55 + N + 5n = 7 + 55 Combine like terms: -55 + 55 = 0 0 + N + 5n = 7 + 55 N + 5n = 7 + 55 Combine like terms: 7 + 55 = 62 N + 5n = 62 Add '-5n' to each side of the equation. N + 5n + -5n = 62 + -5n Combine like terms: 5n + -5n = 0 N + 0 = 62 + -5n N = 62 + -5n Simplifying N = 62 + -5n
| -(x+3y-3)= | | 42-2x=7x+21 | | -5=a-3 | | 12-10x=57-31x | | 46n-2(3n-15)=60 | | y(6y^2-x-1)dx+2xdy=0 | | 3c-12=-5+c | | 46n-2(3n-15)=-60 | | 20-3t=26 | | -12=-4(9+3z) | | .66x+x-4=5(.33x+5) | | 6(y+6)-4=80 | | 2.5x-8=.50(-16+7x) | | 2x+3x-5=15 | | 3d+4d+d-4-2d=0 | | 3x^2+12xy+xy+4y^2= | | -2r+5r-12=-.33(36-9r) | | (5*5)+(5*5)= | | 3x+4(-2x+11)=74 | | .50(4x+18)=2x-9+18 | | 7=3p-8+4p | | 2x+4(-x+2)=18 | | 29+36= | | -3q-5q+10=-6+7q | | -8n+37=-7(n-6) | | -3x^2+18x-2= | | 3+7q=4+6q | | 60000x-3000x^2=0 | | 17.1=5n-1 | | -11n-9(-12-2n)=9(n+2)+8n | | -4x+6(4-2x)=2(x-7)+2 | | -12(1-r)+8(-2r-5)=0 |